1H NMR investigation of paramagnetic chromium(III) olefin polymerization catalysts: experimental results, shift assignment and prediction by quantum chemical calculations$ddedicated to Prof. Roald Hoffmann on the occasion of his 70th birthday - Fernández, Pablo; Pritzkow, Hans; Carbó, Jorge J.; Hofmann, Peter; Enders, Markus (Organometallics, 2007)
The new paramagnetic quinolyl-functionalized Cp chromium(III) complexes 4−8, which serve as precursors for highly active olefin polymerization catalysts, have been synthesized and were investigated together with the known complexes 1−3 by 1H NMR. Full assignment of the observed NMR signals in these systems was achieved by comparison of the different spectra and by spin unrestricted density functional calculations (UB3LYP level) of the Fermi contact term at the hydrogen atoms. All the geometries were optimized using the experimentally determined solid-state molecular structures as starting points. We obtained a very good correlation (r2 = 0.97) between calculated Fermi contact spin densities at the UB3LYP/6-311G(d) level and experimental paramagnetic 1H NMR shifts. Polarization basis set functions at heavy elements are required to reproduce experimental results, whereas polarization functions at hydrogen atoms and/or diffuse functions do not improve the results. The good correlation between calculated and experimental results indicates that the experimental hyperfine shifts are dominated by Fermi contact interactions. Nevertheless, we were able to identify and estimate non-negligible dipolar contributions to the chemical shifts for some protons. It is possible to predict 1H NMR shifts of similar organometallic compounds and to obtain structural information of in situ generated paramagnetic species, which play a key role in several catalytic transformations with paramagnetic catalysts. Additionally, calculations provided us with detailed information of the spin density distribution along the molecular systems.
Published online 25 July 2007
Die Zahl "1" im Ausdruck "1H" ist hochgestellt
Gesehen am 18.11.2022
Keywords: Festschrift